Academic Procrastination and the Architectural Learning Environment among Students with Hearing Disabilities: A Multidisciplinary Perspective (Architecture Image Studies, 2025)
The current study aimed to reveal the relationship between the architectural educational environment and academic procrastination among students with hearing impairments enrolled in integration programs in the Najran region, by adopting a multidisciplinary perspective that combines architectural studies with educational and social sciences. The study adopted a descriptive approach and was applied to a sample of 109 students with hearing impairments, with an average age of 13.0 years and a standard deviation of 1.2, enrolled in integration programs in schools. Data were collected using a questionnaire designed to measure students' perceptions of the architectural educational environment and their level of academic procrastination. The results showed a correlation between certain characteristics of the architectural educational environment, such as spatial organization, visual clarity, ease of movement, and the quality of the spatial experience within classrooms, and students' levels of academic procrastination. The results also indicated that architecturally inappropriate educational environments may be associated with higher levels of academic procrastination, while visually supportive educational environments that take into account the needs of students with hearing impairments contribute to enhancing academic engagement and reducing procrastination behaviors. The study emphasizes the importance of considering the architectural dimension of the educational environment when planning and designing inclusive schools, thereby supporting positive academic behavior and achieving the principle of equal educational opportunities.